Investigating English as a foreign language learners’ perceptions, emotions, and performance during online collaborative writing - Alqasham, Fahd Hamad (Frontiers in Psychology, 2022)
Abstract Drawing on the sociocultural approach, this study aims to explore online EFL learners’ perceptions towards collaborative writing, and the role that learners’ emotions play as factors influencing their collaboration and achievements in face to face and Blackboard Chatbox as applied in their EFL classes. A mixed-methods research approach has been used with a sample of 58 male students enrolled in writing courses at three levels (Levels 1- 3) at the Department of English Language and Translation, Qassim University. Three instruments have been used for data collection; a 45-item closed-ended questionnaire, semi-structured interviews, and the learners' overall performance. The findings show that most learners have positive perceptions towards studying online through Blackboard, and Blackboard Chatbox. Furthermore, Blackboard Chatbox could provide necessary affordances to facilitate learners’ emotion, which could enhance their collaborative writing. However, no significant difference was observed between learners’ performance in the two models of instruction (Sig.= .287). Taken together, the results of the present study enhance current understanding of the role of learners’ emotions in collaborative writing with the use of technology.